2022
DOI: 10.3389/fimmu.2021.803647
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of SARS-CoV-2 Spike Protein Expression in the Silkworm and Induction of Efficient Protective Immunity by Inoculation With Alum Adjuvants

Abstract: The newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is causing a spread of coronavirus disease 2019 (COVID-19) globally. In order to end the COVID-19 pandemic, an effective vaccine against SARS-CoV-2 must be produced at low cost and disseminated worldwide. The spike (S) protein of coronaviruses plays a pivotal role in the infection to host cells. Therefore, targeting the S protein is one of the most rational approaches in developing vaccines and therapeutic agents. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Additionally, the information obtained here is consistent with our recent reports that mice immunized with a combination of the SARS-CoV-2 spike protein and Alum produced neutralizing antibodies in their sera. In contrast, mice immunized with the protein mixed with CFA/IFA did not produce an effective neutralizing response, despite both adjuvants inducing an IgG response [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the information obtained here is consistent with our recent reports that mice immunized with a combination of the SARS-CoV-2 spike protein and Alum produced neutralizing antibodies in their sera. In contrast, mice immunized with the protein mixed with CFA/IFA did not produce an effective neutralizing response, despite both adjuvants inducing an IgG response [23].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that mice immunized with the SARS-CoV-2 spike protein mixed with Alum produced neutralizing antibodies in sera. Sera from mice immunized with the protein mixed with CFA/IFA did not produce an effective neutralizing response, even though both adjuvants inducing an IgG response [23]. Under the circumstances, in this study, our focus is on the various adjuvants that have been previously used to administer antigens to mice.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 strain-specific anti-spike (anti-S) IgG titers were measured with in- house ELISA using trimeric full-length spike proteins generated by a silkworm-baculovirus expression system, as previously described. 13 Briefly, purified target proteins of the WT and Omicron (BA.1) strains were used as coating antigens for ELISA. Optical density at 450 nm (OD 450 nm) and 570 nm (OD 570 nm) was read using a microplate reader after ELISA, and the anti-S IgG titers of each sample were reported as the OD value (OD 450 nm − 570 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Among these systems, the baculovirus–insect cell system has garnered significant attention for the production of recombinant vaccines, and it also offers several advantages over mammalian cells, including high-level expression facilitated by natural origin promoters and post-translation modifications similar to those observed in mammalian cell expression platforms [ 26 ]. The baculovirus expression vector system (BEVS) could develop a relatively quicker method of expression via the cultured lepidopteran cell lines (e.g., Sf9 and Hi-5) or individual insect larvae such as domestic silkworm ( Bombyx mori ) and alfalfa looper ( Autographa californica ), in which recombinant bacmid DNA ( B. mori nucleopolyhedrovirus (BmNPV) or A. californica multiple nucleopolyhedrovirus (AcMNPV)) is transformed or even directly injected without preparation and is being used for VLP-based vaccine production against infectious pathogens [ 7 , 20 , 21 , 22 , 27 ]. Additionally, the co-infection approach using a mixture of different recombinant baculoviruses proves advantageous for generating VLPs requiring multiple structural proteins, such as a non-enveloped virus [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Various Protein Expression Platforms For Vlpsmentioning
confidence: 99%